Implementasi Stem-Edp untuk Meningkatkan Hasil Belajar IPA dan Keterampilan Kolaborasi Siswa: Penelitian - Edelweis I. Tumbelaka; Ferdy Dungus; Fransiska Harahap; Widya A. Tumewu; Mellyatul Aini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research was conducted at SMP Negeri 1 Amurang in class VIII A as an experimental class, with the aim of finding out whether the implementation of STEM-EDP can improve student learning outcomes on the human respiratory system material and student collaboration skills. This study used a Pre-Experimental Design with a One-Group Pretest-Posttest Design for learning outcome tests, and observations for student collaboration skills data. The results of the study on learning outcomes showed that there was an increase in the average student with a pretest score of 25.84 to 86.87 on the posttest. The N-Gain results obtained an N-Gain Score of 0.8236> 0.7 which is included in the high category and an effectiveness interpretation of 82%> 76% which is included in the effective category. The results of the study on collaboration skills obtained pre-experimental values, as many as 3.23% of students were assessed as less collaborative, and 96.77% were assessed as quite collaborative. When conducting the experiment, 25.81% of students were assessed as very collaborative, and 74.19% of students were assessed as very collaborative. Through the analysis of these two variables, it was concluded that science learning outcomes on the human respiratory system material and students' collaboration skills increased after implementing STEM-EDP in learning.